Evolutionary routes to stable ownership - Hare, D; Reeve, HK; Blossey, B (Wiley, 2016)
Ownership can evolve in potentially any species. Drawing on insights from across disciplines, we distinguish between possession and ownership and present species-neutral criteria for ownership, defined as respect for possession. We use a variant of the tug-of-war evolutionary game to demonstrate how ownership can evolve in the form of a new, biologically realistic strategy, Restraint With Retaliation (RWR). In our game, resource holding potential (RHP) is assumed to be equal between interactants, and resource holding asymmetry determines whether ownership is adaptive. RWR will be evolutionarily stable when the ratio of resource holdings between interactants is relatively low, but not when this ratio is sufficiently high. We offer RWR as one evolutionary route to ownership among many, and discuss how ownership unites previously described behavioural phenomena across taxa. We propose that some but not all mechanisms of territory formation and maintenance can be considered ownership, and show that territories are not the only resources that can be owned. We argue that ownership can be a powerful cooperative solution to tragedies of the commons and problems of collective action throughout the biological world. We advance recent scholarship that has begun to investigate the biological importance of ownership, and we call for a comprehensive account of its evolutionary logic and taxonomic distribution. We propose that ownership should be considered a fundamental, unifying biological phenomenon.